The effects of pedometer-based exercise on central and peripheral vascular functions among young sedentary men with CVD risk factors - Omar, Norsuhana; Yeoh, Boon Seng; Chellappan, Kalaivani; Chui, Sara Zijiun; Salamt, Norizam; Aminuddin, Amilia (Frontiers in Physiology, 2023)
Introduction: Cardiovascular diseases (CVDs) remain the main cause of morbidity and mortality in Malaysia and worldwide. This is mainly due to an increase in the prevalence of CVD risk factors such as hypertension, dyslipidemia, smoking, and obesity. Increased physical activity has been recommended as a modality to improve CVD risk. Pulse wave velocity (PWVCF), augmentation index (AI), and finger photoplethysmography fitness (PPGF) index have been introduced to assess the vascular functions related to CVD risk factors. The effects of long-term exercise on PPGF index are not established. Materials and Methods: A total of 70 young men who were sedentary with two or more cardiovascular risk factors were recruited. Subjects were randomly assigned to a control group (CG) (n = 34; no change in walking) and pedometer group (PG) (n = 36; minimum target: 8,000 steps/day). PWVCF and AI were measured via the Vicorder system. The PPGF index was obtained via the finger photoplethysmography method. All parameters were measured at baseline and after 6 and 12 weeks. Results: After intervention, the PG had significant increased step count from 4,996 ± 805 to 10,128 ± 511 steps/day (p < 0.001). The PG showed significant improvement in anthropometric variables, lipid, PWVCF, AI, and PPGF index (time and group effect p < 0.001). No changes were observed in CG. Conclusion: This signifies that pedometer-based walking program is beneficial in improving markers of vascular functions among young working sedentary men with CVD risk factors. Pedometer-based exercise should be encouraged to improve cardiovascular health.